PENYELESAIAN PERSELISIHAN INTERNAL PARTAI POLITIK - M Anwar Rachman (Yuridika, 2016)
This study discusses the Dispute Parties in Indonesia, that is the arrangement of Law and Dispute Resolution Practice According to the Political Parties Act No. 2 Year 2011 concerning Political Parties, as well as the concept of management in the future. The method which use is normative research method concern with three approach, first is statute approach, second is conceptual approach, third is historical approach, forth is case law approach. The results of this study showed that of some Political Parties Act in force in Indonesia none laws governing firmly, clearly and in detail the concept of arrangment dispute Parties. Each order is the old order, New Order, and the Reformation, there are different provisions concerning political party dispute resolution. Almost all of the Indonesian political parties dispute in political or internal conflicts in the body of a political party. Law No. 2 of 2011, which set of settlement of political parties is irrelevant today because, the legal norms in the Law referred double meaning (ambiquity), blurred (absurbty), and it is very broad sense (overbulkiness). In the future need to be more detailed settings related to the legal principles of the Dispute Arrangement of Parties, legal institutions and judges, procedural law, the authority to adjudicate disputes political party.